Does College Influence Sociopolitical Attitudes?. (January 2016) - Campbell, Colin; Horowitz, Jonathan
Past research shows a statistically significant relationship between college completion and sociopolitical attitudes. However, recent scholarship suggests the effects of college on social outcomes may be confounded with unobserved family background. In this study, we leverage the shared family and social background of siblings to better identify the effect of college on sociopolitical attitudes. We draw data from the Study of American Families and General Social Survey and use sibling fixed effects to assess the effect of college on political orientation, support for civil liberties, and beliefs about gender egalitarianism. We find that earning a four-year college degree has a significant impact on support for civil liberties and beliefs about gender egalitarianism, but the effect of college on political orientation is confounded by family background.